Impact of gout on the risk of atrial fibrillation - Kuo, Chang-Fu; Grainge, Matthew J.; Mallen, Christian; Zhang, Weiya; Doherty, Michael (Oxford University Press, 2016)
OBJECTIVES: To examine the risk of atrial fibrillation (AF) at the time of first diagnosis of gout compared with matched controls and to follow incident gout patients and their matched controls after diagnosis to compare their subsequent risk of AF.